(3OjhGf GHf eYJhbs - (3GdehShj , TgGH GdOjf Hf eYJhb GdehShj GdMhjRj, CHh eYJhb,J (B1087 (3g` s ((3eMeO Gejf GdGScfOQGfi s)
(3ChdgG (B:s
(3bGd jeOM QShd Gddg Udi Gddg Ydgj hSde gPG GdYJjb hJdc Te QYGFI aGeRL dLjf GdOeY ai YbjGfI s
(3BNQgG (B:s
(3hdG HQMJ GQGDce hCcace eUGHjMgG JgOi hQGMGFgG fLOi s
(3HgG fXGe GdJYbjHIs
(3Ydjg hba HGSe MceI Gddg Hf YUeJ Gddg GdMSjfis
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B178s
Keywords: (3eJaQbGJs